PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT MENGKONSUMSI OBAT SIRUP YANG MERUSAK KESEHATAN - Achmad Raihansyah Lubis, (Magister Hukum Universitas Semarang, 2023)
This research aims to determine the legal protection efforts that consumers can take and the responsibility that companies must take for losses suffered by consumers due to consuming syrup drugs that damage health. This research explores cases of GGAPA in children that occurred in mid-2022, where consumers suffered losses due to the company's negligence in producing safe medicines for consumers. This case is why it is essential to conduct further research regarding consumer legal protection. This research uses a normative juridical research method, with a statutoryapproach and a case approach. The data in this research is supported by primary data in the form of interviews with one of the mothers of the victim's family who consumed drugs that damaged their health. The novelty of this research is that it discusses the issue of legal protection for consumers and the company's responsibility. The results of this research show that several legal protection efforts can be taken for losses suffered, namely preventive and repressive legal protection efforts, where in this GGAPA case, the victim's family took repressive protection efforts in the form of making efforts to resolve disputes through litigation, namely through class action lawsuit. Consumers also have the right to obtain responsibility from business actors for the losses they suffer, where in this GGAPA case, the victim's family asked for responsibility in the form of compensation through a class action lawsuit.